Analyzing the response of economic growth to monetary policy instruments: The case of Algeria (1990–2024) using the QARDL approach - Belhaoues, Salima; Zohra, Fenazi Fatima; Mohamed, Cherif; Abed, Ali; Guessab, Radhia; Bouzar, Abdallah (The International tax journal, 2026)
This study aims to analyze the response of economic growth to monetary policy instruments in Algeria during the period 1990–2024, focusing on heterogeneity across different growth states, using the quantile accelerated regression with distributed lag (QARDL) methodology. The study relies on quarterly data for a set of key monetary variables, including the exchange rate (tch), interest rate (ir), foreign reserves (cr), and broad money (m2). The results show clear nonlinear relationships in the long term between monetary policy instruments and economic growth, with the exchange rate having a negative and insignificant effect at the lower quantile (0.25) and more negative at the medium (0.50) and high (0.75) quantiles, reflecting the sensitivity of growth to exchange rate fluctuations in cases of medium and high economic performance. In contrast, the short-term results revealed limited positive effects of the exchange rate across different quantiles, indicating a degree of short-term flexibility. The study concludes that it is necessary to enhance the effectiveness of monetary policy instruments, improve the flexibility of the monetary framework, and develop financial markets, thereby supporting the ability of monetary policy to stimulate economic growth in Algeria.